Bacterial Transformations of Naphthothiophenes - Kropp, K. G. (1997)
Naphthothiophenes are minor components of fossil fuels, and they can enter the environment from oil spills. Naphtho[2,1-b]thiophene, naphtho[2,3-b]thiophene, and 1-methylnaphtho[2,1-b]thiophene were synthesized and used in biodegradation studies with 1-methylnaphthalene (1-MN)-degrading Pseudomonas strains W1, F, and BT1. Cultures were incubated with one of the naphthothiophenes with or without 1-MN, acidified, and extracted with CH(inf2)Cl(inf2). The extracts were analyzed by gas chromatography with flame photometric and mass detectors to characterize sulfur-containing metabolites and with an atomic emission detector for quantification. Only strain W1 was able to grow on naphtho[2,1-b]thiophene, but strains F and BT1 cometabolized this compound if 1-MN was present. 1-MN was required by all three strains to metabolize naphtho[2,3-b]thiophene, which was more resistant to biodegradation than the [2,1-b] isomer. Two metabolites of naphtho [2,1-b]thiophene were purified, analyzed by (sup1)H nuclear magnetic resonance spectroscopy, and found to be 4-hydroxybenzothiophene-5-carboxylic acid (metabolite I) and 5-hydroxybenzothiophene-4-carboxylic acid (metabolite II). In cultures of strain W1 grown for 7 days on 52 (mu)mol of naphtho[2,1-b]thiophene, >84% of the substrate was degraded and metabolites I and II accounted for 19 and 9%, respectively, of the original amount of naphtho[2,1-b]thiophene. When 1-MN was present, strain W1 degraded >97% of the naphtho[2,1-b]thiophene and similar amounts of metabolite II were produced, but metabolite I did not accumulate. 1-MN was shown to promote the further degradation of metabolite I, but not of metabolite II, by strain W1. Thus, 1-MN enhanced the biodegradation of naphtho[2,1-b]thiophene. Approximately 70% of the 1-methylnaphtho [2,1-b]thiophene added to cultures of strain W1 with 1-MN was recovered as 4-hydroxy-3-methylbenzothiophene-5-carboxylic acid, the 3-methyl analog of metabolite I. The methyl substitution hindered further metabolism of 3-methyl-metabolite I even in the presence of 1-MN. Cometabolism of naphtho[2,3-b]thiophene yielded two products that were tentatively identified as 5-hydroxybenzothiophene-6-carboxylic and 6-hydroxybenzothiophene-5-carboxylic acids.